Article Review: Antioxidant Activity of Some Plants Found In Garut Arboretum - Asman Sadino; Hesti Renggana; Saepul Nurohman (Universitas Muhammadiyah Sumatera Utara, 2022)
Abstract: Free radicals in the form of atomic molecules do not have partners with high reactivity, free radicals can come from within the body in the form of metabolic waste products and from outside the body such as ultraviolet light, food, beverages, smoke and pollutants. The role of antioxidants is needed to reduce these free radicals. This article review aims to find out and examine scientific information from research that has been carried out regarding plants, especially in the Garut Arboretum which have antioxidant activity. The method of writing this article review uses a literature study through search engines such as Google Scholar, Pubmed, and NCBI. It is known that from 56 plant species found in the Garut Arboretum, 27 plant species have been studied to have antioxidant activity, including 15 plants with very strong antioxidant activity, 9 plants with strong antioxidant activity, and 3 plants with moderate antioxidant activity. Secondary metabolites that are responsible for antioxidant activity include flavonoids, alkaloids, saponins, and tannins.